Enhanced performance of magnetoelectric voltage coefficient in giant magnetostrictive (Ni0.7Mg0.3Fe2O4)/piezoelectric (BaZr0.2Ti0.8O3) composites. (15th November 2022) - Chavan, Pradeep
Abstract: The non-toxic lead-free multiferroic composite samples Ni0.7 Mg0.3 Fe2 O4 /BaZr0.2 Ti0.8 O3 were synthesized by using standard double sintering ceramic method. The composite samples are found to exhibit dielectric response, which might be associated with Maxwell-Wagner type interfacial polarization and Koop's phenomenological theory. The variation of DC conductivity with respect to temperature revealed the conduction of electrons i.e. due to the small polarons hopping mechanism. The synthesized ME composite samples show a representative magnetic hysteresis (M − H) loop type behaviour at room temperature. In a previous report, the response of ME voltage coefficient 4.262 mVcm -1 .Oe was determined for (30%) Ni0.8 Mg0.2 Fe2 O4 + (70%) BaZr0.2 Ti0. 8O3 composites at 5.0 kOe applied DC magnetic field. But in this report, we improved the ME voltage coefficient for the composition 50% (Ni0.7 Mg0.3 Fe2 O4 ) + 50% (BaZr0.2 Ti0.8 O3 ) which is a lead-free ME composite with the massive ME voltage coefficient of 8.562 mV/cm.Oe was achieved. Hence, the estimated results can provide experimental guidance for the optimal design of high-performance magnetoelectric devices and render better support for the technological development in the field of magnetoelectricity. Highlights: Composites exhibit dielectric response under applied frequency. Conduction of electrons was due to the small polarons hopping mechanism. Massive saturation magnetization 16.778 emu/gm was observed. Response of ME voltage coefficient 8.562 mV/cm.Oe was achieved. Observation of giant ME output promise the potential applications.